2012
DOI: 10.1186/1471-2407-12-369
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of miR-100, miR-99a and miR-199b in tissues and plasma coexists with increased expression of mTOR kinase in endometrioid endometrial carcinoma

Abstract: BackgroundAlterations of mTOR gene expression have been implicated in the pathogenesis of endometrioid endometrial cancer however only few studies explored the cause of increased mTOR activation in this malignancy. miRNAs are small, noncoding RNAs, which were proven to regulated gene expression at the posttranscriptional level. The study aimed to explore deregulation of miRNAs targeting mTOR kinase (miR-99a, miR-100 and miR-199b) as a possible cause of its altered expression in EEC tissues. In addition express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 54 publications
6
112
0
Order By: Relevance
“…2). For example, miR-100 could suppress proliferation, induce apoptosis and cell cycle arrest in tumor cells by targeting multiple tumor-related genes such as mTOR, PI3K, AKT1, IGF1-R, HS3ST2, HOXA1, RAP1B, FGFR3, PIK1, Cyr61, FKBP51 [7,58,61,72,75,76,80,87,95]. Direct regulation of some oncogenes involved in tumor cell invasion and metastasis, such as HOXA1, Rac1, ICMT, EphB6, AGO2 by miR-100 has been identified in many cancers [32,41,67,96].…”
Section: The Functions Of Mir-100 and Its Target Genes In Human Cancersmentioning
confidence: 99%
“…2). For example, miR-100 could suppress proliferation, induce apoptosis and cell cycle arrest in tumor cells by targeting multiple tumor-related genes such as mTOR, PI3K, AKT1, IGF1-R, HS3ST2, HOXA1, RAP1B, FGFR3, PIK1, Cyr61, FKBP51 [7,58,61,72,75,76,80,87,95]. Direct regulation of some oncogenes involved in tumor cell invasion and metastasis, such as HOXA1, Rac1, ICMT, EphB6, AGO2 by miR-100 has been identified in many cancers [32,41,67,96].…”
Section: The Functions Of Mir-100 and Its Target Genes In Human Cancersmentioning
confidence: 99%
“…MiR-99a is downregulated in several cancer cell lines and solid tumors including acute lymphoblastic leukemia, 34 hepatocellular carcinoma, 33 prostate cancer, 35 endometrioid endometrial cancer, 32 and lung cancer, 12 but the mechanisms responsible for its downregulation in tumors are still unknown. By overexpression or inhibition, researchers found that miR-99a could suppress cell proliferation, 35 induce G 1 -phase cell cycle arrest, 36 and promote apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Given previous reports showed that mTOR was a direct target of miR-99a in various cancers, 12,32,33 we tended to evaluate whether mTOR signaling was involved in D261-induced G 1 arrest. The predicted consequential pairing of target region of mTOR and miR-99a was shown in Figure 6C.…”
Section: Mir-99a/mtor Axis Is Involved In D261-regulated Cell Growth mentioning
confidence: 99%
“…A combination of miR-199a and miR-542-3p can be used to diagnose endometriosis with a sensitivity of 96.61 % and specificity of 79.66 %, and this approach may serve as a noninvasive marker in practice . Torres et al (2012) found that expression of miR-99a, miR-100 and miR-199b was upregulated in serum of patients with endometrioid adenocarcinoma, and showed that a combination of miR-99a and miR-199b had a higher diagnostic value than each miRNA alone. Analysis of miRNAs in serum in a genome-wide study showed that a combination of four serum miRNAs, miR-222, miR-223, miR-186 and miR-204, can be used to diagnose endometrioid adenocarcinoma with high probability.…”
Section: Application Of Mirna In Endome-trial Cancer As a Biomarkermentioning
confidence: 99%